ANALISIS PENGARUH PENAMBAHAN SIKAMENT-LN DENGAN VARIASI PERSENTASE TERHADAP NILAI SLUMP DAN KUAT TEKAN BETON BERDASARKAN METODE PERAWATAN BETON - Riris Nur Anisah; Yudhi Arnandha; Anis Rakhmawati (FROPIL (Forum Profesional Teknik Sipil), 2022)
Concrete is in great demand because it has good compressive strength. The compressive strength of the resulting concrete is sometimes smaller than the planned compressive strength. Many efforts have been made to fix these problems, one of which is by adding additional materials. In addition to additives, the implementation process of making concrete also have an effect. One of the implementation processes is concrete treatment. In this study, the added material used was Sikament-LN with variations of 0%, 1%, and 2% of the cement weight. The treatment method used is soaking in water and wrapping plastic. Mix planning using the ACI method. The manufacture and testing of test objects is carried out at the Structural Laboratory, Department of Civil Engineering, Faculty of Engineering, Tidar University. The results of the research on the compressive strength of concrete with variations of Sikament-LN 0%, 1%, and 2% by immersing in water were 19.63 MPa, 25.10 MPa, and 26.16 MPa. The compressive strength of concrete with variations of Sikament-LN 0%, 1%, and 2% with plastic wrapping method was 23.43 MPa, 23.16 MPa, and 27.80 MPa. This study concluded that the highest compressive strength of concrete was obtained with the addition of Sikament-LN 2% and the effective method of treating concrete used was the method of immersing in water because the compressive strength of concrete was higher than the plastic wrap treatment method. Key words: concrete, compressive strength, treatment, sikament-LN